Quality of Life in Type 2 Diabetes Mellitus Patients Requiring Insulin Treatment in Buenos Aires, Argentina: A Cross-Sectional Study - Andres Pichon-Riviere; Vilma Irazola; Andrea Beratarrechea; Andrea Alcaraz; Carolina Carrara (Kerman University of Medical Sciences, 2015)
Background Decision-makers have begun to recognize Health-Related Quality of Life (HRQoL) as an important and measurable outcome of healthcare interventions; and HRQoL data is increasingly being used by policy-makers to prioritize health resources. Our objective was to measure HRQoL in a group of Type 2 Diabetes Mellitus (T2DM) patients receiving insulin treatment in Buenos Aires, Argentina. Methods We conducted a cross-sectional study of patients with T2DM over 21 years of age, treated with either Neutral Protamine Hagedorn (NPH) insulin or Insulin Glargine (IG), who had not changed their baseline schedule in the last 6 months. The recruitment was during 2006-7 in nine private diabetes specialists' offices in Buenos Aires, Argentina. A standardized diabetes-specific HRQoL questionnaire, the Audit of Diabetes Dependent Quality of Life (ADDQoL), was used. Results A total of 183 patients were included (93 receiving NPH and 90 receiving IG). The mean QoL score was: 0.98 (SD: 0.89) and the diabetes specific QoL was: -1.49 (SD: 0.90). T2DM had a negative impact on HRQoL with a mean Average Weighted Impact (AWI) score on QoL of -1.77 (SD: 1.58). The greatest negative impact was observed for domains: 'worries about the future', 'freedom to eat', 'living conditions', 'sex life', and 'family life'. The mean AWI score was -1.71 (SD: 1.48) in patients treated with IG and -1.85 (SD: 1.68) in patients receiving NPH, this difference was not statistically significant. Conclusion The ADDQoL questionnaire is a tool that can be used in Argentina to measure the QoL of patients with diabetes when evaluating diabetes care programs. The scores of QoL in our selected population did not differ from those reported in high-income countries. We expect that the results of this study will increase healthcare providers' awareness of patients' perceived QoL and help to overcome the barriers that delay insulin treatment; mainly clinical inertia and patient resistance.